Cherry Picking, Disclosure Quality, and Comprehensive Income Reporting Choices: The Case of Property‐Liability Insurers* - Lee, Yen‐Jung; Petroni, Kathy R.; Shen, Min (Contemporary Accounting Research, 2006)
Statement of Financial Accounting Standards No. 130: Reporting Comprehensive Income encourages enterprises to report comprehensive income on a performance statement rather than on a statement of equity. We investigate the reporting decisions of 82 publicly traded property‐liability insurers that are fairly evenly split in their choice. Our results demonstrate that insurers with a tendency to manage earnings through realized securities' gains and losses (that is, cherry pickers), as well as insurers with a reputation for poor disclosure quality, are more likely to report comprehensive income in a statement of equity. Apparently, these insurers face the highest cost of transparency. We do not find a relation between the reporting decision and the volatility of comprehensive income relative to the volatility of net income. Our findings that insurers' comprehensive income reporting choices are a reflection of their proclivity toward cherry picking as well as their level of disclosure quality should be of interest to standard‐setters because of the controversy over standard‐setters' preference for mandating all firms to report comprehensive income in a performance statement.